Expert opinion on current issues and challenges in irritable bowel syndrome - Lawate, Parimal (International Journal of Advances in Medicine, 2024)
Irritable bowel syndrome (IBS) is a widely prevalent functional gastrointestinal disorder characterized by symptoms such as abdominal pain, irregular bowel movements, and bloating, which significantly impact affected individuals' well-being. The increasing prevalence of IBS in India places a substantial burden on clinical practice. Although diagnostic criteria, such as the commonly used Rome IV criteria, have shown reasonable sensitivity, the diagnosis of IBS remains a nuanced and culturally influenced process. This comprehensive review systematically examines current challenges surrounding IBS prevalence, diagnostic intricacies, and the complex pathophysiology involving visceral hypersensitivity. The review highlights the imperative for noninvasive biomarkers to augment diagnostic precision and emphasizes on following a holistic approach to IBS management as advocated by Indian guidelines. This approach integrates dietary modifications, antispasmodic medications, psychological therapy, and yoga, with specific emphasis on tailoring treatments to individual IBS subtypes. Among antispasmodic drugs, pinaverium bromide because of its unique mechanism of action as a calcium channel antagonist within the gastrointestinal tract has shown promise in alleviating IBS symptoms.